Spatial and temporal characterization of Aedes albopictus oviposition activity in candidate urban settings for sterile insect technique testing in La Reunion Island - Gilbert Le Goff; David Damiens; Abdoul-Hamid Ruttee; Frédéric Jean; Laurent Payet; Cyrille Lebon; Paul Taconet; Benjamin Gaudillat; Nausicaa Habchi-Hanriot; Jean-Sébastien Dehecq; Frédéric Simard; Louis-Clément Gouagna (BMC, 2024)
Abstract Background Understanding of mosquito spatiotemporal dynamics is central to characterize candidate field sites for the sterile insect technique (SIT) testing, and is critical to the effective implementation and evaluation of pilot sterile male release programs. Here, we present a detailed description of Aedes albopictus (Skuse) egg-laying activity over a 6-year period in urban areas identified as potential SIT testing sites on Reunion Island. Method Weekly entomological collections using ovitraps were carried out in residential and adjacent uninhabited habitats in two urban areas, Duparc and Bois Rouge, in the municipality of Sainte Marie, Reunion Island. Time-series data incorporating the frequency of positive ovitraps and the total number of eggs/ovitrap recorded each time at each locality during the study period from May 2013 to December 2018 were analyzed with multifaceted statistical approaches including descriptive statistics and spatiotemporal analyses incorporating the role of climatic factors on overall ovitrap productivity. Results During the ovitrap survey, the proportion of egg-positive ovitraps differed among study sites (χ 2  = 50.21, df = 2, P < 0.001), being relatively lower in Duparc (89.5%) than in Bois-Rouges (95.3%) and the adjacent buffer zone (91.2%). Within each neighborhood, Ae. albopictus egg abundance varied by month in a roughly seasonal pattern marked by a single peak occurring more regularly February each year, a decline at the onset of the austral winter in July, followed by a period of lower ovitrap productivity in August and September. Fluctuation in both positivity rate and eggs densities per ovitraps were related to annual and seasonal variations in local temperature and rainfall (P < 0.001 in all cases). The spatial analysis also captured substantial between- and within-habitats heterogeneity, whereby the overall ovitrap productivity was higher in residential areas than in the buffer zone. Conclusions Collectively, these results reveal that the distribution of Ae. albopictus oviposition activity is shaped by local habitat heterogeneity and seasonal climatic factors. Overall, this study provides baseline insights into the reproductive dynamics of Ae. albopictus, which would assist in planning locally tailored SIT interventions, while addressing concerns related to focal areas of high egg-laying intensity and potential immigration of females from natural areas.